Probing the Brønsted Acidity of the External Surface of Faujasite‐Type Zeolites. Issue 16 (14th July 2020) - Lakiss, Louwanda; Vicente, Aurélie; Gilson, Jean‐Pierre; Valtchev, Valentin; Mintova, Svetlana; Vimont, Alexandre; Bedard, Robert; Abdo, Suheil; Bricker, Jeffery
Abstract: We outline two methodologies to selectively characterize the Brønsted acidity of the external surface of FAU‐type zeolites by IR and NMR spectroscopy of adsorbed basic probe molecules. The challenge and goal are to develop reliable and quantitative IR and NMR methodologies to investigate the accessibility of acidic sites in the large pore FAU‐type zeolite Y and its mesoporous derivatives often referred to as ultra‐stable Y (USY). The accessibility of their Brønsted acid sites to probe molecules (n‐alkylamines, n‐alkylpyridines, n‐alkylphosphine‐ and phenylphosphine‐oxides) of different molecular sizes is quantitatively monitored either by IR or 31 P NMR spectroscopy. It is now possible, for the first time to quantitatively discriminate between the Brønsted acidity located in the microporosity and on the external surface of large pore zeolites. For instance, the number of external acid sites on a Y (LZY‐64) zeolite represents 2 % of its total acid sites while that of a USY (CBV760) represents 4 % while the latter has a much lower framework Si/Al ratio. Abstract : External or internal Brønsted acid sites? Successful attempts to discriminate between the Brønsted acid sites located in the microporosity and at the "external" (i. e. geometric and mesoporous) surface of the most important zeolite structure type currently in use, FAU, are made. Two spectroscopic methodologies (IR and NMR) were developed based on the adsorption of selective bulky probe molecules. Both techniques provide comparable Brønsted acid sites densities.